2000
DOI: 10.1248/bpb.23.602
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationship of Six Glycyrrhiza Species Based on rbcL Sequences and Chemical Constituents.

Abstract: The nucleotide sequences of ribulose-1,5-bisphosphate carboxylase/oxygenase large subunit gene (rbcL) of Glycyrrhiza glabra, G. uralensis, G. inflata, G. echinata, G. macedonica and G. pallidiflora have been determined to construct their phylogenetic tree. Based on these sequences, the six Glycyrrhiza species were divided into two groups: three, G. glabra, G. uralensis, and G. inflata, which produce glycyrrhizin as a major saponin, and the others, G. echinata, G. macedonica and G. pallidiflora, which produce m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 1 publication
3
56
6
Order By: Relevance
“…In the HPLC profile of G. uralensis leaves, three flavanones (1, 2, 5) and two dihydrostilbenes (4, 6) were detected as the major peaks. However, the HPLC profile of the G. uralensis leaves examined in the present study was different from that of G. uralensis leaves (from Chiba University, Japan) reported in our previous paper, 10) in which compounds 1, 2, and 6 were not detected, suggesting that compositions of flavanones and dihydrostilbenes are different among the strains of G. uralensis. In the HPLC profile of the G. glabra leaves, three flavanones 7, 8, and 9 were detected as the major flavanones, these are consistent with those of G. glabra collected in Spain and Sicily.…”
Section: -22)contrasting
confidence: 98%
See 2 more Smart Citations
“…In the HPLC profile of G. uralensis leaves, three flavanones (1, 2, 5) and two dihydrostilbenes (4, 6) were detected as the major peaks. However, the HPLC profile of the G. uralensis leaves examined in the present study was different from that of G. uralensis leaves (from Chiba University, Japan) reported in our previous paper, 10) in which compounds 1, 2, and 6 were not detected, suggesting that compositions of flavanones and dihydrostilbenes are different among the strains of G. uralensis. In the HPLC profile of the G. glabra leaves, three flavanones 7, 8, and 9 were detected as the major flavanones, these are consistent with those of G. glabra collected in Spain and Sicily.…”
Section: -22)contrasting
confidence: 98%
“…In the HPLC profile of the G. glabra leaves, three flavanones 7, 8, and 9 were detected as the major flavanones, these are consistent with those of G. glabra collected in Spain and Sicily. 24) In the leaves of the intermediate-type plants, both G. uralensis-specific compounds (1, 2, 5, 6) and G. glabra-specific compounds (7-9) were detected in different proportions.…”
Section: -22)mentioning
confidence: 92%
See 1 more Smart Citation
“…Amplification and Sequencing of the Ribulose-1,5-bisphosphate Carboxylase/Oxygenase Large Subunit Gene DNA isolation, amplification of the 240-bp DNA fragment covering the two nucleotide-substitutions in the ribulose-1,5-bisphosphate carboxylase/oxygenase large subunit gene (rbcL) of the glycyrrhizin-producing Glycyrrhiza plants, 10) and sequencing of the DNA fragment were performed as previously reported. Table 1 shows the origins of these 10 strains, but their original habitats were unknown.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Thus cultivation of G. uralensis was undertaken to substitute for the wild resources. [4][5][6][7] Extensive chemical studies revealed that the roots and stolons of Glycyrrhiza plants contain not only glycyrrhizin but also many flavonoids, 3,8) including species-specific flavonoids, 9,10) such as glycycoumarin in G. uralensis. In addition, chemical variations in leaves of Glycyrrhiza plants were reported, 11,12) and these variations are useful in identifying the species and strains of Glycyrrhiza plants.…”
mentioning
confidence: 99%